Massive alimentary tract bleeding due to cytomegalovirus infection in an elderly patient - Bora Koc; Huseyin Yuce Bircan; Semsi Altaner; Ozlem Cinar; Umit Ozcelik; Alpaslan Yavuz; Ozgur Kemik (Infectious Disease Reports, 2014)
In recent years, cytomegalovirus (CMV) has been recognized as an important common pathogen in immunocompromized patients. This is due to the increasing number of immunosuppressive medications, intensive cancer chemotherapy use, recurrent transplantations, progressively aging population, and the higher number of human immunodeficiency virus infections. Cytomegalovirus infection especially interests the gastrointestinal tract, anywhere, from the mouth to the anus. Namely, the most commonly affected area is the colon, followed by duodenum, stomach, esophagus and small intestine. The most frequent manifestations of CMV colitis are: diarrhea, fever, gastrointestinal bleeding and abdominal pain. We report here the case of an 82-year-old woman, who was treated for non-Hodgkin lymphoma; she was admitted to the emergency department for abdominal pain and diffuse arthralgia, following massive upper- and lower- gastrointestinal bleeding, due to duodenal and colonic ulcers related to CMV infection.